تولي غير المسلمين الولايات العامة في إندونيسيا : دراسة تحليلية - مقربين، محمد خليل (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The adoption of democratic system in Republic of Indonesia as a form of government requires application of the concept of citizenship and equality among its citizens. This has led to the outbreak of a permanent conflict between scholars and researchers on the issue of public authorities in Indonesia, so that some of them think that non-Muslims are permissible to assume all public authorities (wilayat al-'amah) in Indonesia based on these two concepts, while other think that is impermissible due to the presence of sharia texts indicating that the guardianship of the non-Muslim over the Muslim is prohibited. This is what prompted the researcher to write this research. This research is concerned with studying Islamic legal rulings on Appointment of non-Muslims' into public authorities in Indonesia, by talking about the concept of public authorities, its legal rooting and its legal purposes (maqasid al-shariʻa), as well as the comparison between public authorities in Islamic government system and Indonesian government system. Then the research dealt with Islamic point of view on the concept citizenship and equality which are one of the main principles in democratic system. At the end of the chapter, the research discussed the issue of Islamic legal rulings on non-Muslims' appointment in public authorities in Indonesia, by presenting the opinion of Muslim scholars, mentioning each of their arguments, discussing it, and choosing the preferable opinion. The researcher adopted the inductive-analytical approach to discover general maxims that shape general issues and to generate conclusions on particular objects in this research. Researcher has reached several conclusions: There is a difference between the concept of public authorities in Islamic government system and Indonesian government system in terms of legal sources, purposes, and objectives. The concept of citizenship and equality from Islamic perspective are not rejected concept or invalid, however, these two concepts are defined by restrictions and regulations from the sharia texts or anything based on them. It is not permissible for non-Muslims to assume the public authorities in Indonesia except authorities that are not main position in government, also not related to religious matters or its interests. At the end, the researcher recommends the Indonesian people to gradually apply Islamic law in Indonesia.